Mathematics of bioinformatics : theory, methods, and applications - He, Matthew; Petukhov, S. V. (Sergei Valentinovich) (Hoboken, NJ : Wiley-Interscience, 2011)
'Mathematics of Bioinformatics: Theory, Methods, and Applications provides a comprehensive format for connecting and integrating information derived from mathematical methods and applying it to the understanding of biological sequences, structures, and networks. Each chapter is divided into a number of sections based on the bioinformatics topics and related mathematical theory and methods. Each topic of the section is comprised of the following three parts: an introduction to the biological problems in bioinformatics; a presentation of relevant topics of mathematical theory and methods to the bioinformatics problems introduced in the first part; an integrative overview that draws the connections and interfaces between bioinformatics problems/issues and mathematical theory/methods/applications'--
Includes bibliographical references and index.
Keywords: Biomathematics; Bioinformatics; Computational Biology